The impact of fretting wear on structural dynamics: Experiment and Simulation. (October 2019) - Fantetti, A.; Tamatam, L.R.; Volvert, M.; Lawal, I.; Liu, L.; Salles, L.; Brake, M.R.W.; Schwingshackl, C.W.; Nowell, D.
Abstract: This paper investigates the effects of fretting wear on frictional contacts. A high frequency friction rig is used to measure the evolution of hysteresis loops, friction coefficient and tangential contact stiffness over time. This evolution of the contact parameters is linked to significant changes in natural frequencies and damping of the rig. Hysteresis loops are replicated by using a Bouc-Wen modified formulation, which includes wear to simulate the evolution of contact parameters and to model the evolving dynamic behaviour of the rig. A comparison of the measured and predicted dynamic behaviour demonstrates the feasibility of the proposed approach and highlights the need to consider wear to accurately capture the dynamic response of a system with frictional joints over its lifetime. Highlights: The impact of wear on the dynamics of structures has been experimentally quantified. Wear leads to shifts in natural frequency and damping of structure vibration modes. Wear needs to be included in models to capture the dynamics of jointed structures. A Bouc-Wen formulation is presented to account for wear in dynamic simulations.